Transition-Metal-Free and Selective Deconstructive Carbonyl Olefination of α-Hydroxy Ketones: A Complementary Approach to Knoevenagel Reaction - Sandeep, Sandeep; Saini, Vaneet; Chayawan, Chayawan; Chaudhary, Ganga R.; Venugopalan, Paloth; Kumar, Anil (Synthesis, 2023)
While the carbonyl olefination has been extensively studied and well documented, use of α-hydroxy ketones as precursors for the carbonyl olefination is not reported, till date. Herein, a transition-metal-free and selective Knoevenagel-type deconstructive carbonyl olefination of α-hydroxy ketones using arylacetonitriles under mild reaction conditions is presented. The reaction affords valuable scaffolds of acrylonitriles with the use of α-hydroxy ketones as precursors for carbonyl olefination.
Keywords: deconstructive; carbonyl olefination; α-hydroxy ketones; Knoevenagel reaction